2018
DOI: 10.1093/carcin/bgy079
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen fuels the growth of endometrial hyperplastic lesions initiated by overactive Wnt/β-catenin signalling

Abstract: Unopposed oestrogen is responsible for approximately 80% of all the endometrial cancers. The relationship between unopposed oestrogen and endometrial cancer was indicated by the increase in the number of endometrial cancer cases due to the widespread use of oestrogen replacement therapy. Approximately 30% of the endometrial cancer patients have mutations in the Wnt signalling pathway. How the unbalanced ratios of ovarian hormones and the mutations in Wnt signalling pathway interact to cause endometrial cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Correct regulation of Wnt/β-catenin signaling in this cyclical fashion is required for normal endometrial function [16,17,95,100], as loss of β-catenin results in squamous metaplasia of the endometrium, while constitutively active β-catenin results in endometrial hyperplasia [16,17]. The addition of unopposed estrogen to the models containing activating β-catenin mutations results in EC, demonstrating the relationship between Wnt/β-catenin signaling and hormonal regulation in the endometrium.…”
Section: Tumorigenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Correct regulation of Wnt/β-catenin signaling in this cyclical fashion is required for normal endometrial function [16,17,95,100], as loss of β-catenin results in squamous metaplasia of the endometrium, while constitutively active β-catenin results in endometrial hyperplasia [16,17]. The addition of unopposed estrogen to the models containing activating β-catenin mutations results in EC, demonstrating the relationship between Wnt/β-catenin signaling and hormonal regulation in the endometrium.…”
Section: Tumorigenesismentioning
confidence: 99%
“…This relationship is also highlighted by the fact that progesterone-mediated downregulation of Wnt/β-catenin signaling inhibits EC progression [17]. Progesterone's downregulation of Wnt/β-catenin signaling may play a significant mechanistic role in its treatment effects.…”
Section: Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, β-catenin is the primary mediator of the oncogenic effect in this signaling pathway (17,21). Almost 30-85% of type I EC cases show nuclear accumulation of β-catenin in the epithelium (43)(44)(45). Thus, it is important to understand the role of wnt/β-catenin signaling in EC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to understand the role of wnt/β-catenin signaling in EC. A recent study reported that wnt/β-catenin pathway dysregulation to be an important factor in young EC patients with poor prognosis (45)(46)(47). Genetic mutations of the wnt/βcatenin signaling pathway members are mostly detected in patients with more aggressive histologic type of EC and are related to worse prognosis and poor overall survival rate (4, 10, 45).…”
Section: Discussionmentioning
confidence: 99%